Glucocorticoids modulate macrophage surface oligosaccharides and their bone binding activity. - Bar-Shavit, Z (1984)
The circumstantial evidence that indicates that glucocorticoids (GC) may stimulate osteoclastic resorption in vivo has recently found support in observations that demonstrate that these compounds effectively increase the activity of isolated resorptive cells (osteoclasts, macrophage polykaryons, and elicited macrophages [MO] ) in vitro. Data are presented here that indicate that this stimulation by GC is due to an enhancement of the initial stage of the resorption process, the attachment of cells to bone, and that this is caused by alterations of cell surface oligosaccharides. Specifically, dexamethasone and cortisol enhance by 80% the attachment of MO to bone surfaces in a dose dependent manner but do not alter or reduce the binding of these cells to other surfaces (plastic, collagen, and hydroxyapatite crystals). The effect of GC on cell-bone attachment is blocked by the glycosylation inhibitor, tunicamycin, and the glycosylation modifier, swainsonine; this demonstrates that asparagine-linked oligosaccharides are involved in the stimulatory process. Flow cytometric analysis of GC-treated cells using a panel of fluoresceinated lectins confirms this by indicating a selective, enhanced exposure of plasma membrane-associated N-acetylglucosamine and N-acetylgalactosamine residues, sugars we have previously shown to be pivotal in MO-bone binding. Finally, progesterone, a known GC antagonist, blocks GC-stimulated resorption, macrophage-bone binding, and membrane oligosaccharide modification, presumably by competing for the GC receptor. Progesterone alone alters none of these processes. Thus, GC stimulates the resorptive activity of macrophages by enhancing the initial events in the degradative process (cell-bone binding) and does so, apparently, via receptor-mediator alteration of cell surface glycoproteins.